Sjogren’s disease - epidemiology, etiology, pathogenesis & diagnosis - Carteron, Nancy (Henry Stewart Talks, 2016)
Sjogren's disease: epidemiology, Incidence, Etiology & pathogenesis, Genetics, The neuro-immune interface, Channelopathies, Exocrine gland dysfunction, Diagnosis, Classification criteria, Detection
Archived at 2021/08/29